Acute Lymphoblastic Leukaemia Survival in Children Covered by Seguro Popular in Mexico: A National Comprehensive Analysis 2005-2017 - Paloma Muñoz-Aguirre; Rodrigo Huerta-Gutierrez; Salvador Zamora; Alejandro Mohar; Lourdes Vega-Vega; Juan Eugenio Hernández-Ávila; Evangelina Morales-Carmona; Marta Zapata-Tarres; Sergio Bautista-Arredondo; Ricardo Perez-Cuevas; Roberto Rivera-Luna; Michael R. Reich; et al. (Taylor & Francis Group, 2021)
The aim of the study was to measure survival of children with acute lymphoblastic leukemia (ALL) under Mexico's public health insurance for the population treated under Seguro Popular. A retrospective cohort study using claims data from Mexico's Seguro Popular program, covering cancer treatment from 2005 to 2015 was conducted. Overall 5-year national and state-specific survival for children with ALL across Mexico who initiated cancer treatment under this program was estimated. From 2005 to 2015, 8,977 children with ALL initiated treatment under Seguro Popular. Under this financing scheme, the annual number of treated children doubled from 535 in 2005 to 1,070 in 2015. The estimates for 5-year overall survival of 61.8% (95%CI 60.8, 62.9) remained constant over time. We observed wide gaps in risk-standardized 5-year overall survival among states ranging from 74.7% to 43.7%. We found a higher risk of mortality for children who received treatment in a non-pediatric specialty hospital (Hazards Ratio, HR = 1.18; 95%CI 1.09, 1.26), facilities without a pediatric oncology/hematology specialist (HR = 2.17; 95%CI 1.62, 2.90), and hospitals with low patient volume (HR = 1.22; 95%CI 1.13, 1.32). In a decade Mexico's Seguro Popular doubled access to ALL treatment for covered children and by 2015 financed the vast majority of estimated ALL cases for that population. While some progress in ALL survival may have been achieved, nationwide 5-year overall survival did not improve over time and did not achieve levels found in comparable countries. Our results provide lessons for Mexico's evolving health system and for countries moving toward universal health coverage.